Career entry and initial teacher education: an experience report - Sales, Luana Santos (2025)
This article addresses the initial teacher education process and the early career stage of a Geography teacher, focusing on the construction of practical knowledge and professional development. The beginning of a teaching career is a decisive moment that can lead either to perseverance or disillusionment, as the construction of professional knowledge takes shape from the outset of teaching practice — a period marked by discovery. Considering this, the guiding question is: how is the early career process contributing to the professional development of a Geography teacher working in Basic Education? The objective, therefore, is to present reflections on the early career stage of a Geography teacher and its impact on professional development, with an emphasis on the construction of experiential knowledge. This study adopts a qualitative approach, combining bibliographic research and an experience report. Its theoretical foundation is grounded in the works of Tardif (2007), Huberman (1992), Imbernón (2004), Nóvoa (2009), and Freire (2015). The narratives reveal that experiences gained through participation in teaching initiation programs contributed to both theoretical grounding and practical preparedness for entering the profession. The beginning of teaching emerged as a time of constructing experiential knowledge — challenging, distressing, yet decisive for career retention and influential throughout the professional journey. Based on the report, it was possible to observe that the formative experiences lived at the beginning of the career are foundational to the development of practical knowledge. These forms of knowledge are forged daily amidst uncertainties, challenges, and rituals that shape classroom teaching practice.